Contemporary transcatheter aortic valve implantation related thrombocytopenia. Issue 1 (15th October 2020) - Abu Khadija, Haitham; Ayyad, Omar; Haberman, Dan; Gandelman, Gera; Poles, Lion; Jonas, Michael; Volodarsky, Igor; Kweider, Maher Abu; Maximovskih, Alexander; Shimoni, Sara; George, Jacob; Blatt, Alex
Abstract: Background: Transcatheter aortic valve implantation related thrombocytopenia (TAVI‐rTP) is an inevitable phenomenon. However, no study has been performed on TAVI‐rTP in the current setting of extended clinical indications combined with technology improvements. Methods: Patients with severe symptomatic aortic stenosis who underwent transfemoral TAVI, from January 2016 to December 2019 were enrolled. Results: Two‐hundred and one consecutive patients (mean age 81.1 ± 7.1 years, 96 men) enrolled. Platelet count was recorded before and after aortic valve implantation. Dropped platelet count (DPC) occurred in all but 11 patients who were included. Two groups were created: DPC <30 and DPC ≥30%. DPC was compared with in‐hospital major adverse cardiovascular events. The mean DPC was 26 ± 14%. We found that 67 patients (33.3%) had DPC of more or equal to 30%. In the univariable analysis, the time of the procedure (94.4 ± 32.7 vs 79.4 ± 21.9, p  = .002), the amount of the contrast used (125.4 ± 55.4 vs 108.4 ± 44.1, p  = .02) and the residual AV gradient (13.3 ± 7.2 vs 14.7, p  = .05) were related to a DCP ≥30%. A DPC ≥30% was associated with increased risk of life‐threatening/major bleeding (11.9% vs 1.5%, p  = .001), major vascular complications (16.4% vs 5.2% p  = .009) and death (3.0% vs 0%, p  = .044) at 30 days. After multivariable analysis, the factors associated with a higher DPC were time and contrast. Conclusion: Contemporary TAVI‐rTP in this cohort of patients continues to be a common phenomenon but severe thrombocytopenia is less frequent. Patients developing a DPC ≥30% are associated with poor outcomes at 30 days.